Doppler Echocardiographic Follow-Up of Mitral and Aortic Regurgitation in Children and Adolescents with Subclinical and Mild Rheumatic Carditis - Carvalho,Lelia Maria de Almeida (2017)
Abstract Background: Mild rheumatic carditis (MRC) and subclinical rheumatic carditis (SRC) are basically differentiated through auscultation of mitral regurgitation murmur. The evolution of these forms is not well established in the literature. Objective: To evaluate the evolution of mild and subclinical rheumatic carditis, considering mitral and aortic regurgitation (acute phase) and regression, maintenance or worsening of these diseases at the end of follow-up (chronic phase). Methods: Retrospective, longitudinal study, including patients with mild and subclinical rheumatic carditis. The echocardiographic evolution of mitral and aortic regurgitation was compared in both groups, considering the analysis at the end of follow-up. The Chi-square test and Kaplan-Meier survival curves were used, with significance level established at p < 0.05. Results: A total of 125 patients were included, 69 (55.2%) with subclinical rheumatic carditis and 56 (44.8%) with mild rheumatic carditis, with a mean age in the acute phase of 10.4 ± 2.6 years and, at the end of study, 19.9 ± 4.6 years. The time of follow-up ranged from 2 to 23 years (mean: 9.38 ± 4.3 years). In the acute phase, mild/moderate or moderate mitral regurgitation was more frequent in patients with mild rheumatic carditis (p = 0.001). Mild or mild/moderate aortic regurgitation was also more common in the mild rheumatic carditis group (p = 0.045). In the chronic phase, we observed that both mitral (p < 0.0001) and aortic regurgitation (p = 0.009) were more frequent in patients with mild rheumatic carditis, and survival free of rheumatic heart disease was higher in the subclinical rheumatic carditis group (p = 0.010). Residual mitral regurgitation was higher in the mild rheumatic carditis group p < 0.0001), and residual aortic regurgitation was similar in both groups (p = 0.099). Conclusion: Mitral regurgitation resolution was higher in patients with subclinical rheumatic carditis, and the involution of aortic regurgitation was less frequent and similar in both groups. (Int J Cardiovasc Sci. 2017;30(5):391-400)